Infra-red studies of carbon monoxide and hydrogen absorbed on silica supported metal catalysts - Heal, Martin James (Department of Chemistry, 2016)
The interaction of carbon monoxide and hydrogen on silica supported nickel, cobalt, and iron catalysts was studied using infrared spectroscopy. The products occurring in the gas phase, as well as spectra of adsorbed CO surface species in the frequency range 2300 - 1700 cm−¹ for different order of addition of the two reactants was examined. Bulk powdered samples and conventional thin transparent sample discs were used to study either the products in the gas phase or the adsorbed CO species respectively.